KEBIJAKAN MAJLIS TAFSIR AL-QURâAN (MTA) DALAM PENETAPAN IDUL ADHA - Qusthalaani, Imam (Ahkam: Jurnal Hukum Islam, 2018)
ABSTRACTMajlis Tafsir al-Qurâan (MTA) is one of Islamic organizations established in Indonesia. Although MTA resides in Indonesia, it performs Eid al-Adha by following the determination of Eid al-Adha in Saudi Arabia Kingdom. Muslim scholars agreed that in the implementation of Eid al-Adha in muslim country must be applied in accordance to local mathlaâ. These scholars opinion is in line with the MUI fatwa about the preliminary decision of Ramadhan, Shawwal and Dzulhijjah number 2, 2004 about the preliminary decision of Ramadhan, Shawwal and Dzulhijjah. MTA performs Eid al-Adha by using the announcement of Wukuf Arafah in Saudi because it has no specific method in determining the beginning of the kamariah month. This MTAâs policy is not proper yet in Indonesia and need to be reviewed because the process of the determination does not apply the science of astronomy. MTA also seems to be inconsistent in determining the beginning of kamariah month due to the following two contradictory methods, namely imkan al-rukyah to establish the beginning of Ramadhan and Shawwal and global rukyah to establish Eid al-Adha.Keywords: Majlis Tafsir al-Qurâan, Eid al-Adha, Annaouncement of Wukuf Arafah in Saudi Arabia Kingdom.